Análise estrutural estática por elementos finitos de um chassi veicular tipo spaceframe - (:unkn) unknown (Universidade Federal de Goiás, 2016)
Regarded as the main subsystem of a vehicle, the chassis are the link between the other subsystems and must also support multiple static and dynamic loads with stiffness, reliability and security. In this line, this paper presents the development and analysis of a vehicle three-dimensional structure spaceframe type, due to the complexity of the structure were used computational tooling in order to simulate the behavior of statically tubular structure, with the main objective to certify the reliability of the developed project, ensuring safety to drivers. The structure, existing, was modeled in CAD through SOLIDWORKS software, and their simulations were performed using the finite element method via commercial software ANSYS®. The simulationmethodology had the precise definition of loads and displacement constraints to the model in order to make the most plausible model possible. Were then performed computational analysis of rollover and frontal impact in the model (80 km/h e 60 km/h). Through the simulations, it was possible analyze the displacements arising from the critical situations in which the vehicle was submitted are consistent with what is recommended by regulating rules and bibliographies, with this in view that the chassis developed empirically and computationally simulated showed satisfactory results as its reliability and safety, are not required increment bars or modifying the system geometry.
Structural analiysis by static finite elements of a vehicular chassis type spaceframe
Keywords: Estruturas veiculares; Chassi tubular; Spaceframe; Elementos finitos; Simulação estática estrutural; Car structures; Tubular chassis; Spaceframe; Finite element; Simulation structural static; CIENCIAS EXATAS E DA TERRA::MATEMATICA